An exploration of female physicality and psyche and how these inform art-making - Poole, Tanya Katherine (Rhodes University, Faculty of Humanities, Department of Fine Art, 2000)
This thesis proposes that female physicality informs the psyche and thus in turn, art-making. My argument will be shown to be apposite and informative to the discussion of the work of Paula Rego, Jenny Saville and Cindy Sherman. Furthermore such an understanding is helpful to a reading of my practice. In examining issues of identity, which contribute to the formulation of a distinctly female psyche, I will base my critique on the philosophical positions of Sartre, de Beauvoir and Paglia.
Keywords: Women artists; Women artists -- Psychology; Rego, Paula -- Interviews; Feminism; Women -- Sexual behavior; Sherman, Cindy; Saville, Jenny, 1970-